Illuminating the Territorial Principle In Islamic Criminal Law: An in-Depth Investigation Into Enforcing Islamic Penalties for Non-Muslims - Haq, Islamul; Waeduereh, Mustafakama; Suci, Purnama; Resi, Resi (Jurusan Hukum Tatanegara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin, 2024)
Research Objective: This study examines the Territorial Principle within Islamic Criminal Law, focusing on jurisdictional boundaries and enforcement of Islamic punishments for non-Muslims under Islamic governance. Research Methodology: The research employs literature review methodology, analyzing primary and secondary sources addressing territorial jurisdiction in Islamic legal traditions and examining contemporary implementation case studies. Results: The research identifies divergent jurisprudential positions: Imām Abū Ḥanīfah restricts enforcement to Muslim territories with discretionary authority granted elsewhere, while Imām Malik, al-Syafi'ī, and Imām Ahmad advocate universal application emphasizing individual responsibility over geographical boundaries. Findings and Implications: Implementation of territorial principles in regions like Aceh reveals jurisdictional conflicts between local Islamic law and national legal frameworks, creating inconsistencies that challenge legal coherence within pluralistic governance structures. Conclusion: Diverse interpretations of territorial jurisdiction create practical challenges in contemporary legal systems. Achieving legal harmony requires balancing local religious-legal autonomy with national legal coherence. Contribution: This research provides systematic analysis of territorial jurisdiction principles in Islamic criminal law and their contemporary applications, enhancing understanding of how classical Islamic legal principles operate within modern governance structures. Limitations: The study relies exclusively on literature review methodology without empirical data collection. The research primarily examines theoretical jurisprudential positions rather than comprehensive case studies across multiple jurisdictions. Suggestions: Future research should explore comparative legal mechanisms navigating jurisdictional tensions between religious and secular systems. The study recommends establishing clearer guidelines for territorial application in pluralistic societies, particularly regarding non-Muslim citizens